2018
DOI: 10.1007/s10462-018-9646-y
|View full text |Cite
|
Sign up to set email alerts
|

40 years of cognitive architectures: core cognitive abilities and practical applications

Abstract: In this paper we present a broad overview of the last 40 years of research on cognitive architectures. To date, the number of existing architectures has reached several hundred, but most of the existing surveys do not reflect this growth and instead focus on a handful of well-established architectures. In this survey we aim to provide a more inclusive and highlevel overview of the research on cognitive architectures. Our final set of 84 architectures includes 49 that are still actively developed, and borrow fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
184
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(210 citation statements)
references
References 444 publications
0
184
0
2
Order By: Relevance
“…As noted by Al-Razgan et al [13] in their systematic review of robotics, the field of robotics research has become fragmented. The same can be said of the wider domain of cognitive architectures as noted in the recent survey of the research field [74]. Funding models for research in the domain require that specific engineering solutions to problems be found.…”
Section: Discussionmentioning
confidence: 89%
“…As noted by Al-Razgan et al [13] in their systematic review of robotics, the field of robotics research has become fragmented. The same can be said of the wider domain of cognitive architectures as noted in the recent survey of the research field [74]. Funding models for research in the domain require that specific engineering solutions to problems be found.…”
Section: Discussionmentioning
confidence: 89%
“…A cognitive map or, with a graph-based approach, a cognitive graph can represent parts of systems with a cognitive architecture and in this way be put in one or another cognitive architecture. The work [17] describes some cognitive architectures, the method of description giving an opportunity to think about the compatibility of the presented architectures with the formalism of cognitive maps. The abovementioned work understands the cognitive architectures as software systems that might think about problems in different areas, develop ideas, adapt to new situations, and reflect upon themselves.…”
Section: Related Workmentioning
confidence: 99%
“…Much like knowledge representations for robots, cognitive architectures modularize different components that are central to thoughts, perception, inference, and action and have them connected with one another based on cognitive theories. For an extensive overview of such architectures, we encourage readers who are interested in learning more about them to refer to a review done by Kotseruba and Tsotsos [24]. Within robotics, cognitive architectures are extensively studied in the field of developmental robotics as a means of understanding how we develop sensory and motor skills as an infant.…”
Section: Cognitive Architecturesmentioning
confidence: 99%